A Variational Principle for Three-Point Boundary Value Problems with Impulse - Dianwu Yang (Abstract and Applied Analysis)
We construct a variational functional of a class of three-point boundary value problems with impulse. Using the critical points theory, we study the existence of solutions to second-order three-point boundary value problems with impulse.